Os sentidos atribuídos ao trabalho e a prática docente em Educação Profissional e Tecnológica - Sousa, Daniele Ferreira de (2019)
Upon entering the Post-Graduate Program in Professional and Technological Education (PROFEPT) I saw the opportunity to better study the theme of work and its influence on the individual. In this case, on the teachers who came from the baccalaureate, which we inferred, did not have the pedagogical training to be teachers and did not aim at teaching as a first profession, which raised, among other questions, if the sense that the teacher attributes to the work is in line with the perception of their work as a teacher. Thus, this study aimed to understand if the meanings attributed to work influence the reflection of the teaching practice of teachers of the technical disciplines of Vocational and Technological Education. Qualitative research was carried out with eight bachelors who teach technical subjects at the Instituto Federal do Pará - Ananindeua Campus. Life history was used as a data collection technique. Through a guiding script, teachers were invited to report their professional trajectories, from college entrance to the present day. The analysis of the data followed the theoretical framework adopted in this study, obeying the operation of the hermeneutic-dialectic method. In this way, it was possible to identify the following nuclei: Trajectory until becoming a teacher in EPT; Sense attributed to work; and the Teaching Practice at EPT. We note that teachers, in elaborating the meanings of work and raising questions that relate to teaching practice, are based on their current context, personal, academic and professional trajectory, where the senses and reflections are interwoven in an interchangeable and non-linear process of perceivingbecome teachers. In the face of the analyzes, it was possible to list elements for the elaboration of a support guide that intends to be useful to the teacher in his practice, because, we believe that, with greater appropriation of the themes contained in this one, he can better understand his educational context, its social importance, and with that, to contribute to their formation and affirmation in the teaching profession, especially in the EBTT career.